1996
DOI: 10.1017/s0008197300100492
|View full text |Cite
|
Sign up to set email alerts
|

The Attribution of Culpability to Limited Companies

Abstract: Legally, it is possible to say of a particular company that it is a party to a criminal conspiracy, that it has acted dishonestly or that its conduct in matters of safety is so deficient as to amount to manslaughter. The mechanism which has brought most serious crimes within the competence of companies to commit is, of course, the concept of corporate alter ego or, more precisely, the doctrine of identification. This concept takes the conduct and state of mind of certain high-ranking officials to be the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The new corporate manslaughter offence is intended to reflect the gravity of the harm inflicted in work-related fatality cases (Home Office, 2000, 2005, and it is suggested that the primary shortcoming of existing health and safety offences (which are not consequentialist) is their inability to reflect the harmfulness of work-related fatality cases (Sullivan, 1996;Wells, 2001;Clarkson, 2005;Almond, 2006). We might expect that public attitudes towards these cases would be shaped by the degree of harm involved; many high-profile work-related fatality cases involve multiple fatalities, and would seem to constitute harm-based offences within Warr's dichotomy, thus leading to a public perception that they are serious (Almond, 2008).…”
Section: Discussion: the Implications For The Corporate Manslaughter mentioning
confidence: 99%
See 1 more Smart Citation
“…The new corporate manslaughter offence is intended to reflect the gravity of the harm inflicted in work-related fatality cases (Home Office, 2000, 2005, and it is suggested that the primary shortcoming of existing health and safety offences (which are not consequentialist) is their inability to reflect the harmfulness of work-related fatality cases (Sullivan, 1996;Wells, 2001;Clarkson, 2005;Almond, 2006). We might expect that public attitudes towards these cases would be shaped by the degree of harm involved; many high-profile work-related fatality cases involve multiple fatalities, and would seem to constitute harm-based offences within Warr's dichotomy, thus leading to a public perception that they are serious (Almond, 2008).…”
Section: Discussion: the Implications For The Corporate Manslaughter mentioning
confidence: 99%
“…The introduction of the Corporate Manslaughter and Corporate Homicide Act 2007 into the law of England and Wales represents a notable shift in the way that the criminal law responds to, and categorizes, cases where the activities of a corporate body cause the death of a worker or member of the public. The law has historically struggled to hold corporate defendants criminally liable under the law of manslaughter, and has tended instead to deal with these incidents as regulatory health and safety cases (Clarkson, 1996;Sullivan, 1996;Wells, 2001). The new corporate manslaughter offence introduced by the 2007 Act is intended to 'properly reflect the gravity and serious ness' of work-related fatality cases (Home Office, 2005: 6) by facilitating the successful prosecution of the worst cases under the criminal law of homicide.…”
Section: Introductionmentioning
confidence: 99%
“…There would be little chance of a corporate conviction for an offence of dishonesty in such circumstances. 54 Secondly, this model of corporate liability offers corporations, large and small, perverse incentives to set up convoluted organisational structures designed to avoid criminal liability. 55 Such structures introduce organisational inefficiencies, even if they successfully circumvent criminal liability.…”
Section: Arguments From Consequencesmentioning
confidence: 99%
“…at 102. duty to provide a safe system of work. 128 ÔA breach of this obligation is not just negligence for which the employer is (vicariously) responsible: it is the employerÕs own negligence.Õ 129 Accordingly, the Commission proposed that the corporation would be liable where the death was caused by Ôa failure, in the way in which the corporationÕs activities are managed or organised, to ensure the health and safety of persons employed in or affected by those activities.Õ 130 Far from this basis of liability being obscure, 131 imposing liability on a corporation for its failure to act would actually return the common law of corporate criminal liability to its roots. 132 The underlying basis of such liability was summarised by Professor Sir John Smith QC in his commentary on R v. British Steel plc: 133…”
Section: Corporate Liability For Omissions: the Uk Proposalmentioning
confidence: 99%